STUDI KOMPARATIF ANALISIS SEISMIK PADA STRUKTUR DASAR TETAP DAN DASAR TERISOLASI - misdi, misdi (Jurnal Bidang Aplikasi Teknik Sipil dan Sains (BATAS), 2025)
Many engineers in the world have tried to conduct research to overcome building structures that have been destroyed by sudden powerful earthquakes. One popular method is the base isolation system. This system has proven effective and is an alternative to overcome strong earthquake forces. This method is very suitable to be applied in Indonesia, because Indonesia is classified as an earthquake-prone country. This study analyzes building structures that use base isolators to reduce earthquake forces and compares them with conventional building structures. The earthquake force that enters the building structure can cause multidimensional movements that contribute to horizontal displacement in the x-direction, y-direction and rotational directions, which cause damage to the building structure. The results of the analysis prove that structures that use base isolators can reduce displacement responses (drift stories), it can be seen that the relative displacement between levels after using base isolators becomes smaller compared to fixed base structures. The story shear force can also be reduced, thereby preventing structural damage and casualties